Infra-low frequency neurofeedback in persistent postural-perceptual dizziness—Case report - Sasu, Roxana (Frontiers in Human Neuroscience, 2022)
Infra-Low Frequency Neurofeedback in Persistent Postural-Perceptual Dizziness – Case Study Roxana Sasu Keywords: neurofeedback, dizziness, postural-perceptual, infra-low frequency Abstract: Persistent Postural-Perceptual Dizziness, also known as PPPD or 3PD, is a chronic functional vestibular disorder characterized by persistent sensation of rocking or swaying unsteadiness and/ or non-spinning dizziness without vertigo lasting at least 3 months. Symptoms typically worsen with upright posture (like standing or sitting upright), head or body motion and exposure to busy or visually rich environments. The article describes the application of Infra-low frequency Neurofeedback over 32 sessions on an unmedicated individual with symptoms related to PPPD that were still present 3 years after the initial diagnosis. Along with significant reduction in those symptoms, other accompanying symptoms (like anxiety, intrusive violent thoughts, suicidal thoughts) were markedly improved with ILF NFB. Consistent symptom tracking from session to session, as well as before and after CPT data were used to document reported changes with ILF NFB.